Financial Development and Economic Growth Evidence from Malaysia - Mohamad Yazis Ali Basah; Mazlynda Md Yusuf; Hisham Sabri (Universiti Sains Islam Malaysia, 2024)
For the past decade, a plenty of literature has examined the empirical relationship between economic growth and financial development. An important question of the literature is whether the financial systems influenced growth or vice versa, in the long run. The question of financial development and economic growth is an egg-and-chicken question. Which one comes first, economic growth or financial development? The study seeks to address the question of what is the relationship between financial developments and economic growth in Malaysia. This research study aims to fill the gap and provide the base for further investigation analysis. In this research the writer use dynamic ordinary least square (DOLS) and investigate the relationship between economic growth and financial developments. From (DOLS) model a further investigation of granger causality are also tested to identify direction of causality. The results indicate that there is a weak evidence on long run relationship between economic growth and financial developments. There was no causality relationship between capital market and economic growth however, banking development identified as a lead factor towards economic growth in Malaysia.